EVALUASI PENERIMAAN DAN PENGGUNAAN BERKELANJUTAN SISTEM AUTOMATIC EMERGENCY BRAKING PADA KENDARAAN RODA EMPAT - Ilham Hamzah Saeful, Mochammad
Road Traffic Crashes (RTC) level in Indonesia is adequately prominent, based on the data on BPS (2021) there are 103.645 cases of RTC in Indonesia. Automatic Emergency Braking (AEB) is a technology that can manage to reduce the risk of RTC down until 40%. However, the existence of the technology that can eliminate a lot of risk of RTC does not necessarily change the fact that a lot of Indonesian has not been on the scent of this specific technology. The use of AEB in Indonesia is still very limited due to a certain reason. Therefore, there are some factors that needs to be acknowledged for the continuance intention of use for AEB. In this experiment, the Partial Least Square Structured Equation Model (PLS-SEM) is used to find out what are the factors that could affect the continuance intention of use and how each variable is connected to each other. With a development from a previous Unified Model Driver Acceptance (UMDA) by Rahman, et al. (2018), a model has been established with some additional variables that is considered to be influencing the continuance intention of use for AEB. In order to be able to do the calculation, 156 data had been gathered to be used in the data processing. Measurement model is intended to find out the validity and reliability of the model, as for the structural model is intended to find out the correlation between variables and indicators. There are 19 initial hypotheses for this experiment. However, there are only 12 hypotheses that can be accepted and the rest can not be accepted. The factors that influence continuance intention to use the most are: endorsement, compatibility, satisfaction, and complacent behavior.